Influence of ATII blockers and calcium channel blockers on renal vascular resistance in patients with essential hypertension - Delić-Brkljačić, Diana (Array, 2009)
Abstract: Doppler can evaluate renal vascular resistance, and resistance index (RI) highly correlates with blood pressure and renal function in various pathological conditions. Purpose of the study was to measure and compare renal Doppler indices in patients with newly-diagnosed essential hypertension (EH) and in healthy subjects; to determine changes of Doppler indices in patients after six-months monotherapy with either the AT II blocker (valsartane) or calcium channel blocker (niphedipine); to determine which drug has better renoprotective effect. 65 healthy controls were examined, as well as 69 patients with the newly-diagnosed EH, without signs of the target organ damage. Duplex Doppler US of interlobar intrarenal arteries was performed, and RI, acceleration index (AI) and acceleration time (AT) measured. Antihypertensive monotherapy was performed with vaslartane in 34 patients and with niphedipine in 35 patients. Doppler was repeated after the six-months therapy.